UNIVERSAL LAW WORLD-PANORAMA AS AN IMAGE OF THE FUTURE - Kharchenko, Julia; Kharchenko, Serhii (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The image of the future is presented in both broad and narrow contexts: first, as a set of events of universal significance, and second, as a sequence of occurrences within an individual life. The future is defined as a local period of time following the present moment, filled with a multitude of events that have the potential to occur. The "image of the future" is revealed as a complex construction reflecting multiple dimensions of forthcoming existence. It is confirmed that the rational-logical construction of the image of the future by means of the intellect, on the one hand, contributes to the change and expansion of the "angle of view" covering the material world-panorama. Simultaneously, the world-panorama becomes increasingly multifaceted, far-reaching, and legislatively organized. On the other hand, the unconscious, through intuition, relies on the existing eternal life constants, which in turn support the stability of the world-panorama at the level of the spirit